2020
DOI: 10.1021/acs.jmedchem.9b01617
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene Group, Friend or Foe in Medicinal Chemistry

Abstract: He joined the St. John's University in 2005, where he is currently a Full Professor. He has authored/coauthored over 95 scientific publications including two book chapters. Since 2016, he has been serving as an editorial advisory board member of the European Journal of Medicinal Chemistry. In 2018, he was appointed as an Editor of Bioorganic Chemistry. In 2019, he cofounded start-up company Hysplex LLC. His current research efforts are directed toward the development of small-molecule inhibitors of PARP/HDAC/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 217 publications
1
67
0
Order By: Relevance
“… 44 , 59 As just mentioned for flumioxazin, the presence of other molecules with acetylene groups may result in false positives. Nevertheless, even if it is a moderately common functional group in medicinal chemistry, 60 it may not be considered as a critical issue, as the type and amount of drugs containing acetylene groups administered to a patient is known a priori and the amount of endogenous molecules containing acetylene groups is limited and at much lower concentration than the applied drug. Figure 4 a,b shows the pseudounivariate PLS regression curve of the competitive assay of erlotinib in water using the microfluidic device.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 44 , 59 As just mentioned for flumioxazin, the presence of other molecules with acetylene groups may result in false positives. Nevertheless, even if it is a moderately common functional group in medicinal chemistry, 60 it may not be considered as a critical issue, as the type and amount of drugs containing acetylene groups administered to a patient is known a priori and the amount of endogenous molecules containing acetylene groups is limited and at much lower concentration than the applied drug. Figure 4 a,b shows the pseudounivariate PLS regression curve of the competitive assay of erlotinib in water using the microfluidic device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The alkyne warhead [28] is first converted into a highly electrophilic ketene by a P450 oxidase. Next, the ketene gets attacked by nucleophilic residues of the P450 enzyme leading to a covalent protein‐probe adduct, which can be labeled with a fluorescent dye using Cu I ‐catalyzed azide‐alkyne coupling (Scheme 1).…”
Section: Activity‐based Protein Profiling Of Various Oxidoreductasesmentioning
confidence: 99%
“…TheC P-retaining reactions can be considered as an insufficient release of the MCPs rings train. Therefore,d ifferent to the usual ring-opening reactions of MCPs,t hese CP-retaining reactions are of exceptional value not only because the CP is also as ignificant structure in many bioactive molecules, [7] but also because the remaining CP is still an active moiety having potential applications in synthesis.…”
Section: C Onstruction Of Three-membered Carbocyclesmentioning
confidence: 99%
“…In 2002, Osakada reported that the PtI 2 (PPh) 3 -catalyzedh ydrosilylation reactiono fM CPs 22 (R 1 and/or R 2 = Ar) with silanes 23 led to the carbinyl silanes 24 bearing aC P ring in 27-87% yields [Eq. (7)]. [17] Ther eactions were performed under solvent-free conditions at 80-140 8 8C.…”
Section: C Onstruction Of Three-membered Carbocyclesmentioning
confidence: 99%